Tools, Fertilizer or Cash? Exchange Asymmetries in Productive Assets - Stein Holden; Sosina Bezu (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
We used a field experiment to investigate exchange asymmetries in productive assets among poor rural respondents in Ethiopia. Farmers were randomly allocated two types of productive assets or cash, with a choice to keep the productive asset (cash) or exchange it for cash (productive asset). To introduce productive asset variation, a durable asset (farm tool) and a short-term input (fertilizer) were randomly allocated and combined with a random amount of cash. Loss aversion was proxied with a separate experiment and was used to assess the importance of endowment effect theory to explain exchange asymmetries. A greater exchange asymmetry was found for the more popular tool than for fertilizer. Loss aversion could explain a small but significant part of the exchange asymmetry in tools, but experience did not reduce the exchange asymmetry. Compared to the female respondents, the male respondents exhibited greater exchange asymmetries and more non-linear price responses with declining elasticities as prices increased. Key words: exchange asymmetry, endowment effect, loss aversion, factor markets, productive assets, input demand elasticities, field experiment. JEL codes:
Keywords: D03; D51; O13; Q12; 330; exchange asymmetry; endowment effect; loss aversion; factor markets; productive assets; input demand elasticities; field experiment